Respuestas
Respuesta dada por:
1
Ecuación de la recta que pasa por dos puntos
A(2,3)
↓ ↓
x₁ y₁
B (0,1)
↓ ↓
x₂ y₂
![y-y_{1}= \frac{y_{2}-y_{1}}{x_{2}-x_{1}}(x-x_{1}) y-y_{1}= \frac{y_{2}-y_{1}}{x_{2}-x_{1}}(x-x_{1})](https://tex.z-dn.net/?f=y-y_%7B1%7D%3D+%5Cfrac%7By_%7B2%7D-y_%7B1%7D%7D%7Bx_%7B2%7D-x_%7B1%7D%7D%28x-x_%7B1%7D%29++++)
![y-3= \frac{1-3}{0-2}(x-2) y-3= \frac{1-3}{0-2}(x-2)](https://tex.z-dn.net/?f=y-3%3D+%5Cfrac%7B1-3%7D%7B0-2%7D%28x-2%29)
![y-3= \frac{-2}{-2}(x-2) y-3= \frac{-2}{-2}(x-2)](https://tex.z-dn.net/?f=y-3%3D+%5Cfrac%7B-2%7D%7B-2%7D%28x-2%29)
![y-3=1(x-2)
y-3=1(x-2)](https://tex.z-dn.net/?f=y-3%3D1%28x-2%29%0A)
![y-3=x-2 y-3=x-2](https://tex.z-dn.net/?f=y-3%3Dx-2+)
x-y+3-2=0
x-y+1=0 R//
A(2,3)
↓ ↓
x₁ y₁
B (0,1)
↓ ↓
x₂ y₂
x-y+3-2=0
x-y+1=0 R//
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años